2006
DOI: 10.1111/j.1365-2583.2006.00688.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and expression of a novel gene family showing male germline specific expression in Drosophila melanogaster

Abstract: We report the characterization of two novel genes of Drosophila melanogaster, named mst36Fa and mst36Fb. They define a novel gene family, showing identical time and tissue-specificity limited to male germ cells where their transcription starts during meiotic prophase. These two genes encode for two slightly basic proteins highly homologous to each other and fairly rich in leucine and glutamic acid. Although strictly clustered, these genes utilize different promoter regions as revealed by examination of transge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Northern blot was carried out according to Di Cara et al 2006. The 32 P labeled ix probe was prepared by singlestranded PCR with primer Rev CDS (underlined nucleotides 810-830 in Fig.…”
Section: Northern Analysismentioning
confidence: 99%
“…Northern blot was carried out according to Di Cara et al 2006. The 32 P labeled ix probe was prepared by singlestranded PCR with primer Rev CDS (underlined nucleotides 810-830 in Fig.…”
Section: Northern Analysismentioning
confidence: 99%
“…mst36Fa and mst36Fb are germline male‐specific genes, the transcripts of which appear in the primary spermatocytes and persist until early postmeiotic stages of spermatogenesis (Di Cara et al ., 2006).…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that −500 to +800 and −145 to +10 bp around the mst36Fa and mst36Fb transcription start points, respectively, are sufficient for correct cell‐specific transcription of both reporter gene constructs (Di Cara et al ., 2006). Here we further investigate the size of the mst36Fa and mst36Fb promoters.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations